ANTI-INFLAMMATORY AND ANTIOXIDANT EFFECTS OF AN ETHANOLIC EXTRACT OF THE AERIAL PARTS OF HILLERIA LATIFOLIA (LAM.) H. WALT. (PHYTOLACCACEAE) - Abotsi, Wonder Kofi Mensah; Ainooson, George Kwaw; Woode, Eric (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
Various parts of the perennial herb Hilleria latifolia (Lam.) H. Walt. (Family: Phytolaccaceae) are used in Ghanaian traditional medicine for the treatment of several inflammatory-related disorders. The present study examined the anti-inflammatory effect of an ethanolic extract of the aerial parts of Hilleria latifolia (HLE) in acute and chronic inflammation models. Since free radicals and reactive oxygen species are implicated in inflammatory diseases, the antioxidant potential of HLE was also investigated in in vitro experimental models. HLE (10-300 mg kg-1, p.o.), either pre-emptively or curatively, significantly inhibited carrageenan-induced foot oedema in 7-day old chicks. Similarly, the NSAID diclofenac (10-100 mg kg-1, i.p.) and the steroidal anti-inflammatory agent dexamethasone (0.3-3 mg kg-1, i.p.) dose-dependently reduced the oedema in both pre-emptive and curative treatments. In the Freund’s adjuvant induced-arthritis model in rats, HLE as well as the positive controls, dexamethasone and methotrexate, showed significant anti-arthritic properties when applied to established adjuvant arthritis. HLE (10-300 mg kg-1, p.o.) significantly reduced oedema in the ipsilateral paw of rats but failed to prevent systemic arthritic spread. The DMARD methotrexate (0.1-1 mg kg-1, i.p.) and dexamethasone (0.3-3 mg kg-1, i.p.) reduced significantly the total polyarthritic oedema as well as the spread of the arthritis from the ipsilateral to the contralateral paws of the treated animals. The extract (0.03-1.00 mg ml-1) exhibited Fe3+ reducing activity, scavenged DPPH and prevented lipid peroxidation. These findings suggest that the extract exerts in vivo anti-inflammatory activity after oral administration and also has antioxidant properties which may contribute to its activity.